2011
DOI: 10.1038/sj.bdj.2011.769
|View full text |Cite
|
Sign up to set email alerts
|

Oral health awareness in adult patients with diabetes: a questionnaire study

Abstract: outcomes and increase mortality. 6 However, a meta-analysis reported that treatment of periodontal disease by scaling/root planning and oral hygiene in people with diabetes resulted in a mean reduction in HbA1c levels of 0.4%. 7 Despite growing evidence about the associations between oral health problems in patients with diabetes, there is limited research investigating oral health awareness in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 13 publications
9
74
3
1
Order By: Relevance
“…Or it could simply be that many dentists do not take on the responsibility of providing oral hygiene education and advice. Similar findings have been reported in many previous studies (Allen et al, 2008;Al Habashneh et al, 2010;Bahammam, 2015;Bowyer et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Or it could simply be that many dentists do not take on the responsibility of providing oral hygiene education and advice. Similar findings have been reported in many previous studies (Allen et al, 2008;Al Habashneh et al, 2010;Bahammam, 2015;Bowyer et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Poor oral health knowledge and awareness of the relationship between diabetes mellitus and oral health problems have been found in most of the previous studies in different areas worldwide (Yuen et al, 2009;Bowyer et al, 2011;Eldarrat, 2011;Al Habashneh et al, 2009;Allen et al, 2008). Allen et al (2008) reported that Al Amassi and Al Dakheel 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, regardless of the well-known negative consequences of diabetes on oral health, many previous studies revealed that most of the diabetic patients did not have enough knowledge about the negative impacts of diabetes on their oral health [17-20]. At the same time, many studies highlighted the fact that diabetic patients have more knowledge about the systemic consequences of diabetes than about diabetes-related oral complications [19, 21].…”
Section: Introductionmentioning
confidence: 99%
“…3 Poor control of blood sugar can cause progression of gingivitis, alveolar bone loss, salivary gland dysfunction and impaired sense of taste and mouth feel. 4 Acidity of saliva in patients with type 1 diabetes is a strong factor in reducing the buffering capacity of saliva and thus increasing the risk of tooth decay. 2 The risk of tooth decay in patients with diabetes is significantly greater than the controls that is because of reducing the ability of saliva in cleaning, neutralizing and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%